PENATALAKSANAAN TEKNIK LOTUS BIRTH PADA PERSALINAN DI KLINIK SHANTY MEDAN - Elvalini Warnelis Sinaga; Sundari Putri Wijaya (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Ante-Natal Care (ANC) is a health service by professionals provided to mothers during pregnancy which is carried out in accordance with antenatal care standards. The delay in cutting the umbilical cord is to leave the umbilical cord uncut for at least 1 hour which is believed to increase immunity in newborns. This study aims to conduct advanced midwifery care with a delay in cutting the umbilical cord at the Shanty Clinic. The research method is a case study. Management is carried out with a continuous of care approach, namely midwifery care for Ny. A G1P0A0 starting from Pregnancy, Childbirth, BBL, Postpartum and Family Planning at the Shanty Maternity Clinic. Comprehensive midwifery care for Mrs.